2015
DOI: 10.1111/bph.13336
|View full text |Cite
|
Sign up to set email alerts
|

Loss of 5‐lipoxygenase activity protects mice against paracetamol‐induced liver toxicity

Abstract: BACKGROUND AND PURPOSEParacetamol (acetaminophen) is the most widely used over-the-counter analgesic and overdosing with paracetamol is the leading cause of hospital admission for acute liver failure. 5-Lipoxygenase (5-LO) catalyses arachidonic acid to form LTs, which lead to inflammation and oxidative stress. In this study, we examined whether deletion or pharmacological inhibition of 5-LO could protect mice against paracetamol-induced hepatic toxicity. EXPERIMENTAL APPROACHBoth genetic deletion and pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 51 publications
1
31
1
Order By: Relevance
“…Real-time PCR and chromatin immunoprecipitation (ChIP) assay were performed as described (26,27). Primer sequences are listed in Supplementary Tables 2 and 3.…”
Section: Real-time Pcr and Chromatin Immunoprecipitation Assaymentioning
confidence: 99%
“…Real-time PCR and chromatin immunoprecipitation (ChIP) assay were performed as described (26,27). Primer sequences are listed in Supplementary Tables 2 and 3.…”
Section: Real-time Pcr and Chromatin Immunoprecipitation Assaymentioning
confidence: 99%
“…The LOXs pathway is involved in the metabolism of leukotrienes and has been implicated in hepatic inflammation and liver damage [48]. Interestingly, further studies by Li et al [49] revealed that inhibition of LOX pathway attenuates acute liver failure by inhibiting macrophage activation, while Pu et al [50] demonstrated the critical role of 5-LO activity in PCM-induced liver injury by regulating paracetamol metabolism and oxidative stress. It was found that pharmacological inhibition of 5-LO in mice markedly ameliorated PCM-induced liver injury while inhibition of 5-LO induced hepatoprotective effect, which was associated with induction of the antitoxic phase II conjugating enzyme (sulfotransferase2a1), suppression of the pro-toxic phase I (CYP3A11), and reduction of the hepatic transporter (MRP3).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report 47 showed that a lack of the 5-LOX gene and pharmacological inhibition of 5-LOX synthase reduce APAP-induced liver injury, as demonstrated by decreases in the ALT level and hepatic necrosis. The protective effect of 5-LOX inhibition on APAP hepatotoxicity is attributed to attenuation of APAP bioactivation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%